Business model of a selected type of applications - Maher Soliman Awad, Ahmed (2023)
In the fast-paced and competitive mobile app market, selecting an effective monetization strategy is crucial for app developers seeking to achieve success. This study contributes to the existing research on mobile app monetization models by examining their impact on the likelihood of app success. By analyzing a diverse dataset of mobile apps across various categories, this research aims to provide valuable insights into the relationship between different monetization strategies (including in-app purchases, ads, paid, free, both free and paid options, freemium, and subscription) and the likelihood of achieving app success. Utilizing binary logistic regression and controlling for important variables such as user ratings, app category, and market competition, the analysis reveals nuanced associations between monetization models and app success. The findings challenge conventional assumptions and offer a fresh perspective on the complex dynamics of monetization within the mobile app market. This research fills a significant research gap and contributes to a better understanding of the factors that influence mobile app success, providing actionable insights for app developers, marketers, and industry professionals.